Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.